Implementasi Tempat Sampah Pintar Berbasis IoT di Desa Tawangbanteng - N Nelis Febriani SM; Dede Rizal Nursamsi; Dimas Nurjaman; Iin Inayatul Hidayah; Sintia Yolanda (Yayasan Pemimpin Inovasi Science, 2025)
Waste management is a crucial issue in various regions, including Tawangbanteng Village, Tasikmalaya Regency. This Community Service activity aims to provide a solution to waste management problems through the development and implementation of an innovative tool called TRIOERY (3 in 1 Recycle). TRIOERY is an Internet of Things (IoT)-based smart trash can that integrates three functions in one system: an organic waste bin for compost production, a recycling bin that provides points as an incentive for residents, and a waste incinerator with minimal smoke emissions. In addition to the technological aspect, this program also focuses on strengthening human resource capacity through education and training on effective and sustainable waste management. Training is provided to local communities to become more environmentally conscious and able to sort and manage waste independently. The results of this activity show an increase in public awareness of environmental cleanliness, efficiency in household waste management, and the emergence of new economic opportunities, especially in supporting environmentally-based MSMEs. With the implementation of technology and a participatory approach, this program is expected to become a waste management model that can be replicated in other rural areas with similar problems.